Loneliness in prison - Schliehe, Anna K. (European journal of criminology, 2022)
At first glance, contemporary prisons are environments defined by an ?enforced collective? (Goffman, [1961] 1991) and prisoners are, if anything, plagued by ?life en masse? (Sykes, 1958), yet the depth and weight of loneliness in prison can be intense. Prisons are often associated with metaphors of loneliness, disruption and empty time, and, as Armstrong (2018) highlights, imprisonment is an exemplary symbol for being stuck in space and time. Based on empirical data from a study of imprisonment in England & Wales and Norway, in this article we analyse several forms of loneliness found in prisons and beyond, from the visceral, immediate sense of being physically alone and separated from loved ones to the ethical or existential experience of abandonment and hopelessness. We conclude by pointing to the fact that the two otherwise very different penal contexts yield similar findings when it comes to the experiences of loneliness. This implies that the sense of not fitting in, of being ?ethically alone? (Stauffer, 2015) and essentially misrecognized (Lister in Fraser and Bourdieu, 2007), goes beyond specific prisons and jurisdictions. We also note that, as well as evoking feelings of loneliness, in some circumstances imprisonment can provide some respite from it.